Innovative Behavior of State Vocational School ASN Teachers in Minahasa District - Palangda, Listriyanti; Sumual, Herry; Sumual, Shelty D.M.; Kaligis, Jenny Nancy (JR Education, 2025)
This study aims to analyze the influence of teamwork, organizational culture, self-efficacy, achievement motivation, and transformational leadership on teachers' innovative behavior through job satisfaction as a mediating variable in State Vocational High Schools (SMKN) of Minahasa Regency. This study uses the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method to test the direct and indirect relationships between research variables. This study uses a quantitative approach with a purposive sampling technique, involving SMKN teachers in Minahasa Regency as respondents. Data were collected through questionnaires and analyzed using PLS-SEM, which allows the evaluation of the measurement model and the causal relationship between the research variables. The results of the analysis show that teamwork, organizational culture, self-efficacy, achievement motivation, and transformational leadership have a significant influence on teachers' innovative behavior. In addition, job satisfaction acts as a mediator in the relationship between independent variables and teachers' innovative behavior. Among the variables studied, transformational leadership and self-efficacy have the most dominant impact on teachers' job satisfaction and innovative behavior. These findings indicate that increasing innovative teacher behavior can be achieved by strengthening transformational leadership, building a conducive organizational culture, increasing teacher self-efficacy and achievement motivation, and creating high job satisfaction. Therefore, educational policies and school management strategies need to focus on these factors in order to improve the quality of teaching and innovation at SMKN Minahasa Regency.